ABOUT THE SYSTEM ANALYSIS OF UNEMPLOYMENT OF YOUTH: GENERAL TASKS AND PRIVATE MODELS OF MARKET INDICATORS - Natalia V. Kontsevaya; Irina V. Orlova (Статистика и экономика)
In this work attempt of system approach to the analysis of labor market of youth is made, the place and a role of youth labor exchange are dened, opportunities and methods of state regulation are opened, contradictions in the analysis of the main market indicators are designated.Within system approach to the analysis of dynamics of market processes modeling of the main indicators of labor market in regional scale is shown.This approach can be useful when developing effective and economically reasonable mechanisms of employment of youth, both at the level of regional services of employment, and in the state scale